Same but different: A new possible scheme on late archaic black-figure vases - Joháczi, Szilvia; Párkányi, Bence (Dissertationes Archaeologicae, 2024)
Attic black-figure vases from the Late Archaic and Early Classical periods are often neglected by scholars. Most of them are not included in the Beazley Archive Pottery Database, significantly hindering related research. This paper presents such a vase from the collection of the Museum of Fine Arts in Budapest. The authors propose that the scene on the lekythos, akin to others from the era, is a simplified version of a more elaborate one.